2017
DOI: 10.1186/s12879-017-2429-2
|View full text |Cite
|
Sign up to set email alerts
|

Clindamycin-rifampin combination therapy for staphylococcal periprosthetic joint infections: a retrospective observational study

Abstract: BackgroundStaphylococcal species account for more than 50% of periprosthetic joint infections (PJI) and antimicrobial therapy with rifampin-based combination regimens has been shown effective. The present study evaluates the safety and efficacy of clindamycin in combination with rifampin for the management of staphylococcal PJI.MethodsIn this retrospective cohort study, patients were included who received clindamycin-rifampin combination therapy to treat a periprosthetic hip or knee infection by Staphylococcus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 32 publications
2
22
2
1
Order By: Relevance
“…One possible explanation is that staphylococcus more easily forms a biofilm on the surface of the implants, as well as its drug‐resistance to antibiotics . Novel materials, such as α‐tocopheryl acetate and α‐tocopheryl phosphate, have been observed to be able to prevent biofilm formation by Staphylococcus aureus , which is encouraging, as these materials may act as promising tools to be incorporated into the DAIR procedure. For streptococcal infections, our limited data demonstrated a generally satisfactory success rate of 71.4% (5/7 cases), which was still higher than the data from a multicenter study (35%, 11/31 cases).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…One possible explanation is that staphylococcus more easily forms a biofilm on the surface of the implants, as well as its drug‐resistance to antibiotics . Novel materials, such as α‐tocopheryl acetate and α‐tocopheryl phosphate, have been observed to be able to prevent biofilm formation by Staphylococcus aureus , which is encouraging, as these materials may act as promising tools to be incorporated into the DAIR procedure. For streptococcal infections, our limited data demonstrated a generally satisfactory success rate of 71.4% (5/7 cases), which was still higher than the data from a multicenter study (35%, 11/31 cases).…”
Section: Discussionmentioning
confidence: 68%
“…All 3 cases with Staphylococcus aureus infections were successfully treated, and even for methicillin‐resistant staphylococcus, as was observed in our 9 MRSE infections, the use of DAIR completely eradicated the infections. These data were similar to those in a report by Leijtens et al ., which demonstrated a 78% success rate (14/18 cases) for acute staphylococcal PJI . Staphylococcal infections have been viewed as being a risk factor for failed DAIR, as the literature has reported a high failure rate, ranging from 45% to 76% (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that clinical resistance of certain organisms develops more rapidly to RFP compared to many other drugs . As such, recommendations for RFP use are always accompanied by the admonition of combination, not sole, therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, in these cases, rifampin should not be administered. In several observational studies over the following years, the success rate in patients with PJI treated with a defined duration of rifampin combination therapy ranged between 55% and 100% (61,64,66,(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84). This wide range still triggers the discussion on the divergence of outcome results.…”
Section: Rifampin In Staphylococcal Pji In Humansmentioning
confidence: 99%
“…Thus, other oral combination partners such as trimethoprim-sulfamethoxazole, clindamycin, minocycline, linezolid, and fusidic acid have been proposed. In a retrospective study, 18 patients with PJI treated with DAIR and a clindamycin/rifampin combination had a cure rate of 78% (82). Tornero et al (73) showed a lower success rate with the addition of an antibiotic whose level is decreased by rifampin interaction (linezolid, trimethoprim-sulfamethoxazole, or clindamycin) compared to that of the fluoroquinolone combination, with remission in 13 of 21 patients (61.9% remission) versus 49 of 54 patients (90.7% remission).…”
Section: Mode Of Administration and Rifampin Dose And Combination Agementioning
confidence: 99%